2023
DOI: 10.1097/ncc.0000000000001209
|View full text |Cite
|
Sign up to set email alerts
|

The Feasibility and Acceptability of a Needs-Oriented Psychoeducational Intervention Among Caregivers of Adolescent and Young Adult Cancer Patients

Abstract: Background: Little is known about the psychoeducational interventions for caregivers of adolescent and young adult (AYA) cancer patients. Objective: To evaluate the feasibility and acceptability of a needs-oriented psychoeducational intervention among caregivers of AYA cancer patients. Methods: In this 2-arm (parallel-group), pilot randomized controlled trial, participants were randomized to the intervention or control group. Participants in the control group received usual care, whereas those in the intervent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 35 publications
1
8
0
Order By: Relevance
“…In addition to usual care, participants in the intervention group received the PEI, which was delivered by the principal investigator (PI) (Q.C.). The details of the development and delivery procedure of the intervention were described in the previous pilot study . In brief, according to stress and coping theory, caregivers’ unmet needs and coping strategies were 2 modifiable factors that were targeted to improve their health outcomes .…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…In addition to usual care, participants in the intervention group received the PEI, which was delivered by the principal investigator (PI) (Q.C.). The details of the development and delivery procedure of the intervention were described in the previous pilot study . In brief, according to stress and coping theory, caregivers’ unmet needs and coping strategies were 2 modifiable factors that were targeted to improve their health outcomes .…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, guided by stress and coping theory, we developed a PEI to address this gap. The theoretical framework and the rationale for this intervention have been described previously …”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…They found that what caregivers needed most was observing the patient condition and the knowledge of preventing disease recurrence. Chen et al [17] surveyed 195 primary caregivers of patients with esophageal cancer and found that 90.3% of the caregivers needed nutritional guidance, and 65.1% of them hoped for personalized bedside nutritional guidance.…”
Section: This Study Was Funded By National Natural Science Foundation...mentioning
confidence: 99%